ENHANCING CITIZEN AND CASEWORKER EXPERIENCE: A CHATBOT SOLUTION FOR MERATIVE CÚRAM CITIZEN ENGAGEMENT AND CASEWORKER PORTALS - Sudhakar Mattem (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The Merative Cúram platform plays a vital role in government health and human services programs, yet navigating its complexities presents challenges for both citizens and caseworkers. This article introduces an AI-powered chatbot solution designed for the Citizen Engagement Portal and Caseworker Portal, aimed at optimizing service delivery, reducing workloads, and enhancing data management efficiency. The solution leverages natural language processing, machine learning, and real-time data integration to provide guided application assistance, instant case updates, and comprehensive policy support. Implementation results demonstrate significant improvements in application processing accuracy, citizen satisfaction, caseworker productivity, and operational cost savings across participating agencies.